1999
DOI: 10.1105/tpc.11.9.1665
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of AvrXa10 Can Be Replaced by the Transcriptional Activation Domain of VP16 from the Herpes Simplex Virus

Abstract: The avirulence gene avrXa10 of Xanthomonas oryzae pv oryzae directs the elicitation of resistance in a gene-for-gene manner in rice lines carrying the resistance gene Xa10. We have localized a transcriptional activator domain in the C terminus of AvrXa10 by using amino acid replacement mutagenesis. One mutant, with replacements at three hydrophobic amino acid residues in the C-terminal domain, was defective for transcriptional activation in yeast and avirulence activity in rice. The activation domain from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 44 publications
(82 reference statements)
1
45
1
Order By: Relevance
“…It should also, be noted that tomato Bs4 is exceptional because it is the only known R gene that mediates recognition of TALE mutant derivatives (14,15). In contrast, the TALE-specific R genes Bs4C and Bs3 from pepper, as well as Xa27, Xa7, and Xa10 from rice, collectively fail to recognize the aforementioned TALE mutant derivatives (8,9,(11)(12)(13). Thus, the RNA-seq approach we report should be applicable to most TALE-specific plant R genes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It should also, be noted that tomato Bs4 is exceptional because it is the only known R gene that mediates recognition of TALE mutant derivatives (14,15). In contrast, the TALE-specific R genes Bs4C and Bs3 from pepper, as well as Xa27, Xa7, and Xa10 from rice, collectively fail to recognize the aforementioned TALE mutant derivatives (8,9,(11)(12)(13). Thus, the RNA-seq approach we report should be applicable to most TALE-specific plant R genes.…”
Section: Discussionmentioning
confidence: 86%
“…Expression of such executor type R proteins triggers a programmed cell death, referred to as the hypersensitive reaction (HR) that effectively stops disease progression (5). Previous studies have shown that TALE mutant derivatives that lack either their NLS or AD are generally incapable of triggering matching plant R genes (8,9,(11)(12)(13). Thus, transcriptional activation of R genes may be the most common mechanism for recognition of TALEs.…”
mentioning
confidence: 99%
“…Notably, the aviruence (avrxa5) gene corresponding to xa5 is a member of the AvrBs3 protein family whose products can be secreted into the host cells from the bacteria to trigger the hypersensitive response (HR; Hopkins et al 1992;Rossier et al 1999). The HR induction by the ArvBs3, AvrXa10, and AvrXa7 proteins is dependent on their nuclear localization signals (Zhu et al , 1999Van den Ackerveken et al 1996;Yang et al 2000), and their AAD that could interact with TFIIA small subunit as suggested by a coimmuno-precipitation assay (Kobayashi et al 1995). In addition, some AvrBs3 family proteins have been shown to bind to double-stranded DNA (Yang et al 2000) and specifically up-regulates genes during infection and in the resistance reaction mediated by Xa27 (Marois et al 2002;Gu et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…malvacearum were expressed in the plant cells (15,56). In a separate study, we have observed a 75% reduction in the number of transformation foci after particle bombardment of resistant rice leaves with a plant-expressed copy of avrXa10 (66). Therefore, the protein products of avrXa10 and avrXa7 along with possible virulence factors are likely to be secreted by a hrpencoded type III secretory apparatus into the cells of the rice plant.…”
Section: Discussionmentioning
confidence: 99%